The Grammar of Israeli Settler Colonial Violence and the Genocidal War Waged on Gaza: from the Nakba to the 7th of October 2023 - El Sakka, Abaher (PARTECIPAZIONE E CONFLITTO, 2025)
This article analyses the official and unofficial Israeli discourse(s) towards Palestinians since October 7, 2023. These discourses are separate from established historical colonial ones, but the article sheds light on the shifts in semantic structures and uses pertaining to meanings and connotations. First, the article offers examples of official Israeli speeches outlining fundamentally colonial discourses when it comes to arguments and narratives re-employed in the current context of the genocide. Thus, the article examines discourses that fall within the binary structures of the ordinariness of evil; good and evil; progress and savagery; enlightenment and darkness (immorality), and the ’animalization of the Palestinians’. This logic of binarity facilitates calls for forced displacement, urbicide, domicide, annihilations of families, the killing of children, deprivation of food, water and fuel, closures to aid, bombings of cemeteries and hospitals, bombings of Islamic and Christian places of worships, killings of paramedics and volunteers in civil protection and humanitarian aid. Second, the article examines genocidal warfare, which relies on the negation of the existence of Palestinians as a people and community, and the dehumanization’s process which allows for the destruction of the land and the people of Palestine. In particular, the article looks at the violence organized against Palestinians of the West Bank since 7th of October, by interrogating the speeches that accompany such acts of violence undertaken by both settlers and military forces. The focus lies on the analysis of the socio-political backgrounds of actors and the discursive and material mobilization of Israeli parties and organizations.